The barriers and facilitators of Iranian men's involvement in perinatal care: a qualitative study - Sepideh Hajian; Nahid Mehran; Masoumeh Simbar; Hamid Alavi Majd (BMC, 2022)
Plain language summary Men's participation in the perinatal period can reduce the problems of this period and leave a good memory for the whole family. In this phenomenological qualitative study, through in-depth interviews, participants were asked to express their experiences and views on men's participation in the perinatal period and the factors that increase and decrease their participation. Finally, the data were analyzed using the proposed method of Graneheim and Lundman and MAXQDA software. Interviews were conducted with 21 people (data saturation limit) and the data were classified into 3 main categories and 12 sub-categories. The results revealed that men face a dual mechanism in participating in perinatal care, in which some of these factors can facilitate their participation and others can reduce it.